Computer Engineering and Technology 19th CCF Conference, NCCET 2015, Hefei, China, October 18-20, 2015, Revised Selected Papers - Xu, Weixia; Xiao, Liquan; Li, Jinwen; Zhang, Chengyi (Communications in Computer and Information Science,, 2016)
This book constitutes the refereed proceedings of the 19th CCF Conference on Computer Engineering and Technology, NCCET 2015, held in Hefei, China, in October 2015. The 18 papers presented were carefully reviewed and selected from 158 submissions. They are organized in topical sections on processor architecture; application specific processors; computer application and software optimization; technology on the horizon.